A fuzzy incidence coloring to monitor traffic flow with minimal waiting time. (30th December 2021) - Yamuna, V.; Arun Prakash, K.
Abstract: In this paper we measure the Fuzzy incidence chromatic numbers of certain Fuzzy incidence graphs. We apply Fuzzy incidence coloring to real-world problems to monitor human loss during accidents by adhering to traffic flow laws and in particular, reducing traffic flow waiting times.